Identifikasi Turunnya Kinerja Cargo Handling pada Proses Reliquefaction Gas di Kapal LPG/C Gas - Darmana, Eka; WK, Wendy (Marine Science and Technology Journal; Vol 1 No 1 (2020): Marine Science and Technology Journal, 2020)
Reliquefaction plant is a machine system that have function to maintain pressure in the cargo tank. And has an important role in the process of cargo handling to keep cargo in a liquid state. The problems that occur in the reliquefaction plant will result in a decline in the performance of the cargo handling process which will result in hampered vessel operational activities. The observation was carried out at LPG / C GAS WALIO which is a ship owned by PT. PERTAMINA. The source of the data obtained by the author is obtained by direct observation at the research site and direct interviews with gas engineers and engineers at the research site. In addition, data sources are also obtained from manual books on the ship. The results of the study stated that the decline in cargo handling performance in the gas reactivity process was caused by several factors including: less than the maximum compression of the cargo compressor, lack of the amount of sea water circulated into the system and the lack of vacuum in the cargo condensor. These things result in not achieving the ideal temperature on the chargo and the process of reliquefaction takes a long time.